Indirect signs of blunt duodenal injury on computed tomography: Is non-operative management safe?. Issue 1 (January 2016) - Bradley, Matthew; Bonds, Brandon; Dreizin, David; Colton, Katharine; Shanmuganathan, Kathirkamanthan; Scalea, Thomas M.; Stein, Deborah M.
Abstract: Introduction: Clear signs of duodenal injury (DI) such as pneumoperitoneum and/or oral contrast extravasation mandate laparotomy. Management when computed tomography (CT) reveals indirect evidence of DI namely duodenal hematoma or periduodenal fluid is unclear. We evaluated the utility of indirect signs to identify DI and the success of expected management, hypothesizing patients with indirect evidence of DI on CT can be safely managed non-operatively. Methods: We retrospectively reviewed patients with a computed tomography (CT) scan with periduodenal hematoma or periduodenal fluid treated between January 2003 and January 2013 at a level 1 Trauma Center. Demographics, injury characteristics, laboratory values, injury severity scores (ISS), and outcome measures were recorded. Patients having immediate laparotomy were compared to those initially managed nonoperatively. Results: We identified 74 patients with indirect signs of DI, with 35 patients (47%) undergoing immediate operative exploration and 39 (53%) initially managed non-operatively. Lactate (4.5 mg/dL, standard deviation (SD) 2.1 vs 3.1 mg/dL, SD 1.4, p  < 0.001), ISS (median (IQR) 34 (27–44) vs. 24 (17–34), p  = 0.002) and abdominal AIS (3 (3–4) vs 2 (2–3), p  < 0.001) were higher in those with immediate operation. The incidence of DI requiring operative repair was 11% (8 of 74). Six of 35 (17%) explored urgently had a DI requiring repair while 29 of 35 (83%) had no DI or minor injury not requiring surgical therapy. Of those managed non-operatively, 7 of 39 (18%) failed observation but only two (5%) required duodenal repair. There was no significant difference in intensive care unit (ICU) (10.2 days, standard error [SE] 2.1 vs 9.7 days, SE 4.8, p  = 0.93) or hospital (22.5 days, SE 3.8 vs 23.6 days, SE 8.5, p  = 0.91) length of stay between those operated on immediately and those that failed non-operative management when adjusted for age, sex, and ISS. There was no mortality in the non-operative group related to an intra-abdominal injury. Conclusion: Observation of patients with indirect sign of DI fails in about 20% of patients, but failure rate due to DI is low at 5%. Conservative management in appropriately selected patients is reasonable with close observation.